Design for the Future Essay: Retail Banking and Financial Service Under System Analysis - Hung Lee, Sheng (UNIVERSIDAD DE SONORA, 2023)
Financial planning services and banking experience are complicated systematic social-technological design challenges more than only discussing numbers, money, investment, and benefit. Thus, the purpose of the research is to apply modified System-Theoretic Process Analysis (STPA) to study retail banking and financial service through the lens of service systems to empower us to have more holistic views to consider other critical aspects of services and systems. Following a Capital One Café model as our case study, we identified ten key controllers/stakeholders and their values and goals in the retail banking system and then translated the outcomes into losses and system-level hazards and constraints, which helped us generate high-level, detailed hierarchical control structures to enable us to analyze the topic from the perspectives of customers, banking service provider, and retail. Under STPA systematic approach of analyzing the retail banking experience and financial services, we conclude three learnings from service designer’s perspectives: 1) establish meaningful bonding’s between retail and financial services, 2) create service roles to deliver a better and more immersive user experience, and 3) translate service touchpoints to data points to improve service quality.